The complete chloroplast genome sequence of Athrotaxis cupressoides - Zhitong Han; Jialiang Li; Kangshan Mao (Mitochondrial DNA. Part B. Resources, 2021)
Athrotaxis cupressoides (Cupressaceae) is a Tasmanian endemic conifer. It is mainly threatened by habitat fragmentation and limited distribution, yet little is known about its genomic background. In this study, the complete chloroplast (cp) genome of the species was assembled and annotated. The cp genome of A. cupressoides is a circular of 134,248 bp in size, where the inverted repeat regions (IRs) were lost. A total of 112 unique genes were annotated, including 78 proteins-coding genes, four rRNA genes, and 30 tRNA genes. The maximum likelihood (ML) phylogenetic tree indicates that the subfamily Athrotaxidoideae, to which A. cupressoides belongs, is sister to a clade including four subfamilies including Sequoioideae, Taxodioideae, Cupressoideae, and Callitroideae. The complete cp genome will be helpful to further studies on the conservation of this species and the evolutionary history of Cupressaceae.